A SNP uncoupling Mina expression from the TGFβ signaling pathway. Issue 1 (2nd October 2017) - Lian, Shang L.; Mihi, Belgacem; Koyanagi, Madoka; Nakayama, Toshinori; Bix, Mark
Abstract: Introduction: Mina is a JmjC family 2‐oxoglutarate oxygenase with pleiotropic roles in cell proliferation, cancer, T cell differentiation, pulmonary inflammation, and intestinal parasite expulsion. Although Mina expression varies according to cell‐type, developmental stage and activation state, its transcriptional regulation is poorly understood. Across inbred mouse strains, Mina protein level exhibits a bimodal distribution, correlating with inheritance of a biallelic haplotype block comprising 21 promoter/intron 1‐region SNPs. We previously showed that heritable differences in Mina protein level are transcriptionally regulated. Methods: Accordingly, we decided to test the hypothesis that at least one of the promoter/intron 1‐region SNPs perturbs a Mina cis‐regulatory element (CRE). Here, we have comprehensively scanned for CREs across a Mina locus‐spanning 26‐kilobase genomic interval. Results: We discovered 8 potential CREs and functionally validated 4 of these, the strongest of which (E2), residing in intron 1, contained a SNP whose BALB/c—but not C57Bl/6 allele—abolished both Smad3 binding and transforming growth factor beta (TGFβ) responsiveness. Conclusions: Our results demonstrate the TGFβ signaling pathway plays a critical role in regulating Mina expression and SNP rs4191790 controls heritable variation in Mina expression level, raising important questions regarding the evolution of an allele that uncouples Mina expression from the TGFβ signaling pathway. Abstract : Mina is a ubiquitously expressed JmjC family 2‐oxoglutarate oxygenase with pleiotropic roles in cell proliferation, cancer, T cell differentiation, pulmonary inflammation, and intestinal parasite expulsion. Although Mina expression varies according to cell‐type, developmental stage and activation state, its transcriptional regulation is poorly understood. Our report demonstrates that the TGFβ signaling pathway plays a critical role in regulating Mina gene expression and that SNP rs4191790 controls heritable variation in Mina expression level.